Combination of metformin and gallic acid induced autophagy and apoptosis in human breast cancer cells - Marziyeh Haghshenas; Negar Firouzabadi; Amin Reza Akbarizadeh; Marzieh Rashedinia (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Breast cancer is the most common type of cancer and one of the major causes of death among women. Many reports propose gallic acid as a candidate for cancer treatment due to its biological and medicinal effects as well as its antioxidant properties. This study aimed to assess the effects of metformin and gallic acid on human breast cancer (MCF-7) and normal (MCF-10) cell lines. Experimental approach: MCF7 and MCF-10 cells were treated with various concentrations of metformin, gallic acid, and their combination. Cell proliferation, reactive oxygen species (ROS), as well as cell cycle arrest were measured. Autophagy induction was assessed using western blot analysis. Findings/Results: Metformin and gallic acid did not cause toxicity in normal cells. They had a stronger combined impact on ROS induction. Metformin and Gallic acid resulted in cell cycle arrest in the sub-G1 phase with G1 and S phase arrest, respectively. Increased levels of LC3 and Beclin-1 markers along with decreased P62 markers were observed in cancerous cells, which is consistent with the anticancer properties of metformin and gallic acid. Conclusion and implications: The effects of metformin and gallic acid on cancerous cells indicate the positive impact of their combination in treating human breast cancer.